Determinants of Consumer Satisfaction in Increasing Electric Car Purchase Decisions: The Role of Technology Adoption as a Moderating Variable in Jakarta - Gibson Manalu; Slamet Riyadi; Sukesi; Bambang Raditya Purnomo (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: The electric vehicle (EV) market in Jakarta has grown rapidly, with BEV sales increasing significantly between 2020 and 2025. However, the factors influencing consumer satisfaction and purchase decisions remain unclear, particularly regarding service quality, product innovation, price, and technology adoption in the EV market context. Method: This study employed a quantitative approach with an explanatory research design. A total of 224 respondents were selected using purposive sampling from BEV users in Jakarta. Data were collected through structured online questionnaires consisting of 65 items. Data analysis was conducted using Moderated Regression Analysis (MRA) and the Sobel Test to examine mediation and moderation effectsare. Results: The findings reveal that service quality (β = 0.411; p = 0.000), product innovation (β = 0.280; p = 0.019), and price (β = 0.188; p = 0.048) have significant positive effects on consumer satisfaction. Furthermore, service quality (p = 0.035), product innovation (p = 0.049), and price (p = 0.000) significantly influence purchase decisions. Consumer satisfaction significantly mediates the relationship between service quality and purchase decisions (p = 0.029), as well as product innovation and purchase decisions (p = 0.090). Technology adoption was found to significantly moderate the relationships between service quality, product innovation, price, and purchase decisions (p < 0.05). The model demonstrated strong explanatory power with an Adjusted R² value of 0.617, indicating that 61.7% of the variance in purchase decisions is explained by the proposed model. Conclusion: The study concludes that service quality, product innovation, and price significantly influence consumer satisfaction and EV purchase decisions in Jakarta. Consumer satisfaction mediates these relationships, while technology adoption strengthens the influence of marketing factors on purchase decisions. The novelty of this study lies in the role of technology adoption as a moderating variable in the EV market context.